Persis Local Government (Frataraka) Coins - amir amirinezhad; صلاح الدین معروفی; مریم رحمن ستایش (مجله مطالعات ایرانی, 2019)
1. Introduction The history of Persis (local Persian kings) during Seleucid and Parthian dynasties has reconstructed more likely on classification and study of their left over coins. As Achaemeniad Empire fell down and Seleucid and Parthian dynasties rose, Fars State announced its autonomy for a while, and the rulers were local governors. Pre-Sassanid coins are the most important documents of the era which could give a better understanding of the region. As for the classification of coins, the first group introduces four kings who have called themselves “Frataraka”. These coins are similar to the Achaemeniad coins indicating the affiliation of Frataraka to that big dynasty. There are also signs of typical Seleucid styles and coins.   2. Methodology  With a documentary study of Frataraka coins, the present article aimed to examine lines and motifs depicted on these coins and accordingly find an answer to the question over the lines and motifs of Frataraka coins. The present article has carried out as a field and library study in order to discuss the question with a correct theory. The theory says the lines and motifs of coins resulted by the recreation of historical memory of Frataraka toward the bright past of Achaemeniad dynasty.   3. Discussion    According to the historical documents, Alexander of Macedon, in his attack on Iran and its capture, implied the most severe blows to the Persian body and suppressed any opposition and riot against him in the area (Plutarch, 1990, 7-456; Olmstead, 1993, 2-721; Wilken, 1997, 4-193). After the death of Alexander about 323 B.C., his commanders started fighting each other well known as Diadochoi. There was a fight between two famous commanders of Alexander (Eumenes and one-eyed Antigone) in Susiana and Media in which Antigone won and minted coins in Susa in 316-318 B.C. (Bellinger, 1950: 45). Peucestas, one of famous Alexander commander, was the Persis ruler back then who adopted soft policy towards the natives, with the Persis background. He empowered Persis authorities and shared his power with them (Bevan, 1902: 42). Strabo suggests that Persia was tributary to Macedonia (Edson, 1958: 158). Seleucus, in the Western parts of the empire, conquered Mesopotamia in 312 B.C. and fought against Antigone in in Ipsos battle in 304 B.C. and he managed to win the battle, conquered Persia, and established Seleucid dynasty. He minted coins in 300 B.C. in Susa and Pasargadae (Jenkins, 1978: 198). These events reflect the removal of Peucestas in Persis. Though it is not clear when exactly Persis tried to revive its power, there is little information available on relationships between Seleucus and Antiochus I with Persis. It can be said that, because of the marriage between Seleucus and Apameh, daughter of Spitamenes, the relationships can be considered good, it could put the Seleucus legitimacy among the people in danger as there was no Persian race sensitivity (Wiesm,ehöfer, 2009, 37). Seleucus in 281 B.C. put his son Antiochus as the ruler of Asia and he went to Macedonia. Antiochus set up so many cities and colonies and the remains of Hellenistic pottery in Takht Hill and Pasargadae and Zahak Hill enclosure in South West of Shiraz show that the Seleucids established colonies in the region (Mohamadifar, 2015: 151). Antiochus I was killed in 261 B.C. in Sardis while suppressing a local riot (Rajabi, 2002: 34). Antiochus II also known as Theus (God) sat on the throne as his father successor. He then was poisoned to death by his wife Laodice to make Seleucus II, also known as Callinicos (lustrous conqueror), sat on the throne. What Herzfeld wrote about the history of Persis shows that the Persis kings established the Frataraka government in 300 B.C. But Herzfeld was not sure about the exact date, as he mentioned the date to be 150 B.C. Based on the discovered Frataraka coins by Herzfeld, Newell suggests the relative independence date to be 280 B.C. He adds the successors of Alexander went into war to seize power and the Frataraka seized the opportunity to mint coins and could keep its semi-independence rule before the Molon uprising. Hill suggests the first Frataraka that is Bagadat coin minted in 250 B.C. (Hill, 1967, 397-405). However, Koch believes that Bagadat has carried out his nationalist movement in the half of third century B.C. (Koch, 1988, 89-95). Nevertheless, he does not regard it as a complete independence. DeMorgan and Stiehl, based on the coins from the Frataraka, suggest it to be 220 B.C. (Stiehl, 1959, 375-379). Therefore, he has considered the Persian massacre coincided with the emergence of Bagadat and it was after Antiochus that he has minted coins. Concluding the theories discussed, it was not possible for the nationalism of Frataraka to be occurred before the time of Seleucus I, as the historical books suggest there were the Macedonian rulers of Persis before 312 B.C. Schmitt believes that Persis has been ruled by the great Antiochus’ supporters but he reveals no new evidence for confirmation (Schmitt, 1964, 50). The present research, with the historical events in this period, suggests that Bagadat could not mint the first Persis coins before the killing of Antiochus I in 261 B.C., on the other hand, during the post-Antiochus I that the Persian natives had military and royal positions (it was common to empower the Persian natives since Peucestas) seized the opportunity and controlled the region during the reign of Antiochus II and they announced independency and minted coins due to the weakness of the Seleucid kings and civil wars during the reign of Seleucus II and III (246 B.C – 223 B.C.). Historical events especially the Ptolemy III’s attack to Persis, Media and Susa and weakness of Seleucid government and Parthian revolt in East indicate that there was local government in Persis. In other words, just saying that Bagadat minted coins in 220 B.C. could not have historical support as the historical books mention Iskandar, he was the ruler of Persis who led a riot against Antiochus III helped by his brother and ruler of Median ruler Molon. The king of Egypt, Ptolemy III (238 B.C.) fought against the Seleucus II, passed the Euphrates and conquered Mesopotamia, Babylon, Susa, Persepolis (Pars) and Media. Arsaces seized the opportunity to defeat Andragoras and claimed the throne. Seleucus managed to compromise with Ptolemy and went eastward about 238-9 B.C. and could not do much deal and Tiridates established Parthian dynasty building the city of Dara or Darium (Gotschmidt, 2009: 54-57). Antiochus III, also known as the Great Antiochus, rose to power in 223 B.C. In his reign, Molon, the Median ruler helped by his brother Iskandar, the Persis ruler, run riot and took the throne. Wiesehofer recalled the riot to be in 205 B.C. (Wiesehofer, 2007:40). He easily conquered Babylon, Eritrea Sea bank (Persian Gulf and Oman Sea), Susa (excepting Susa enclosure) and nearly Mesopotamia. The king alerted and he personally intervened to suppress Molon and managed to defeat him near the city of Apolloniatis. The uprising shows that the Seleucids have controlled Persis years before 220 B.C. Afterwards, Antiochus went eastward and convinced Arsaces to surrender and made them tributary to himself. However, war against the Romans warned the end of Antiochus power. In a war about 190 B.C. in Magnesia (Anatoly), Antiochus defeated by the Romans and accepted the heavy terms of Apame peace treaty (188 B.C.). To pay the tribute to the Romans, Antiochus marched out to Susa and Persis in 187 B.C. He intended to loot the Bell Temple in Elymais (Holleaux, 1942 : 254). However, he confronted with the resistance of Susan natives. It predisposed the riots of Susa and Ajapir (Izeh) which ultimately Elymaian established a local government in 147 B.C. led by Kamnaskires. The weakness of Antiochus III since 190 B.C. until his attack in 187 B.C. and the start of civil revolts in Susa made a proper ground for Artaxerxes I to mint coins in Persis. According to the historical events, his coins could not have been minted during the authority of Antiochus III (before 190 B.C.). At the other hand, years after 175 B.C. are the authority of the Antiochus IV that the historical books show he conquered Armenia, Media and the Persian Gulf shores. This charge of Antiochus IV occurred before 162 B.C. Then with the historical events the minting date of Artaxeres I coins can be considered about 190 B.C. to 175 B.C. (Amirinezhad et al. 2015: 14). Antiochus IV (Epiphanies) who was a competent king sat on the throne in 175 B.C. He organized the ruling financial affairs; then charged his army across the Euphrates to raise the taxes. He first came to Armenia, though they apparently were belong to the new king of Seleucid dynasty but actually refused to obey the king’s orders. Antiochus charged to the Persian Gulf shores to lead Persis once he conquered Armenia and Media. This charge of Seleucid king indicates that the Seleucids had not ruled Persis during 187 B.C. to 175 B.C. Antiochus IV attacked the Temple of Nanaya in Elymais about 162 B.C. but his charge did not work and the settlers took up guns and prevented the desecration to the temple. Therefore, the Seleucid king forced to withdraw empty handed and went to Persis. He got sick along the way and passed away in the city of Gabiana. As Polybius, Diodorus and Appiano quoted, Antiochus passed away due to a deadly disease reveled by the heaven (Kennedy Eddie, 2002: 184). Death of Antiochus started the fall of Seleucids so that civil wars and royal disagreements were at their peak with Antiochus V sat on the throne, it coincided with the minting of first Elymais local government coins in Ayapir and Susa. The historical books illustrate the years after 162 B.C. full of chaos and massacre in territories ruled by the Seleucids. Demetrius killed Antiochus IV brutally, and Alexander Ballas killed Demetrius in Syria in 150 B.C. This period (162 B.C – 150 B.C.) is the most logical time for minting the Vahuburze coins due to the excessive weakness of Seleucid kings and their attention to the western lands, as they could not mint coins before 162 B.C. due to the authority of Antiochus IV. At the other hand, in the years after 150 B.C., Alexander Ballas’ attack to Susa and Persis has been mentioned in the historical books and then he conquered Persis and Elymais. Therefore, it is more likely that Vahuburze coins were minted during 162 B.C. – 150 B.C. Polianus quoted in the Seventh book that the Macedoniam ruler of Persis thought of killing 3000 Persians. He gathered and lured them with some excuses rounded by an army of 300 cavalries and 3000 heavy infantries and massacred them. Polianus added Vahuburze scattered 3000 Greek soldiers among the Persian people and put them in the Persian houses and ordered to massacre them overnight (Wiesehöfer, 2009, 73-74). The present research believes that this massacre by the Seleucids could only happen during Alexander Ballas reign as the historical books and minted coins by the king in Susa indicate that Alexander Ballas conquered Susa once again and subjugated the Elymais. It occurred during 150 B.C. – 147 B.C. as Demetrius II helped by the Egyptian king (Ptolemy Moheb al-Om) started a long battle against Alexander Ballas around Western parts of Seleucid empire in 147 B.C. Departure of Alexander Ballas to the West parts put the East parts in turmoil. In these days, Elymais established a local government in which Kamnaskires minted coins as the leader. Mehrdad charged his army to the North and West parts of Iran and Autophradates I become the Persis ruler and his coins could be minted from 147 B.C. to 129 B.C. onward as before these days the dominance of Alexander Ballas on East and North parts of Persian Gulf is final. The Parthian Mehrdad marched to the Media in 147-8 B.C. and he conquered it about 144 B.C. and seized the Seleucid with an attack on Babylon in 141 B.C., so that the dated coins of Mehrdad minted in 138-139 B.C. and 139-140 B.C. in Seleucid confirmed the event. Mehrdad retruned to Hirkani after the battle ended. About 140 B.C. due to the requests by Macedonians and Greeks settled at the Upper Satrap such as Babylon for Demetrius II in Syria and, at the other hand, disaffection of Demetrius to stay in Syria led him to think to retake the lost lands. Demetrius charged to the East and entering Mesopotamia passed Babylon. He won battles against the Parthian. The Persian led by Autophradates I hoped to gain its full independency and rejecting tribute to the new rulers, the Iranian Najd (Parthian) came to help Demetrius II to battle the Parthian. However, he was unlucky in the decisive and final battle about 131 B.C. The Parthian general charged at him with some tricks, routed his troops and captured the Seleucid king. Then he wandered the king around the Parthian cities and sent him to Hirkani with Mehrdad. Mehrdad treated Demetrius well, engaged his daughter Roodgooneh to him and sent him to Gorgan. Mehrdad attacked the local governments due to their collaboration with Demetrius II and the Khong-e-Noroozi stone in Malmir plain recorded the victory of Mehrdad over Elymais as it says “Mehrdad the King of Kings” (Saraf, 1993:59). At the other hand, his minted coins have found in Susa but the Parthian king kept the local rulers in their local governments (Kawami, 1987:6; Colledge, 1977:10). Antiochus VII Sidetes in 129-130 B.C. went into war with the Parthian outreaching them under the pretext of freeing his brother (Meyer, 1969:64). Houghton (1983: 101) believes that the Parthian controlled Susa until 130 B.C. but Antiochus VII conquered it for one year. During his war with the Parthian, the Seleucid army ordered by Antiochus deployed at Media and Persis for winter. The deployment and food shortage led the Seleucid army to suppress the Median and Persian natives. If we refer to the Ploianus report once again, it would justify the massacre of Seleucid army carried out to revenge the killings of 3000 Persian army and it is more likely done in Autophradates I, as the historical books and events suggest the revenge carried out by the Whwbrz successors (e.g. Autophradates). The Seleucid army defeated in 129 B.C. and Antiochus committed suicide because he did not bear the defeat. Once Farhad II defeated Antiochus, we witnessed coins under the name of Farhad II in Susa and Elymais. It was after the war that the Scythians battle with the Parthian in the West area and the Parthian king forced to confront them at that area. The Parthian army failed to do anything against the Scythians and the Parthian king killed in the battle. Autophradates announced full independence with the weak Parthian government and lack of Seleucid power in the region, so that Fravahr symbol as monarchy on Autophradates coins confirms the event. Therefore, it is more likely to believe that the first three kings of Frataraka (Bagadat, Artaxerxes and Whwbrz) had semi-independent government. Struggling for independence paid for during Autophradates I and the full independence was in place until the end of Autophradates government. Starting the second period of Persis kings during the Autophradates II, Persis kept running as semi-independent state under the Parthian rulers (Sellwood, 1994, 406). At this time, the new rulers took power in Persis who chose the title of Melaka on their coins that were essentially different with the previous coins and it perhaps represents the new dynasty other than the Frataraka (Kennedy Eddie, 2002, 97-98).   4. Conclusion The Frataraka were the local kings of Persis, which preserved with full awareness of traditions and political and religious symbols used in Achaemenid Empire and transferred them to the next generation (Sassanid) in more evolved formation to introduce the religious political system in new harmony mould in Sassanid world leadership system. The political religious symbols used in the Frataraka coins are similar in meaning and concept. The Bagadat coins were the first Persis coins. They minted in two sets. The throne symbols with lotus in king’s hand like the motif of Great Darius in Persepolis, as it seems the Persis king (Bagadat) wants to remind his power to the foreigners with this image and as the holy structure, flag and his motif as a worshiper tries to present his legitimation among the people with his originality and also introduce himself with the flag as a follower of powerful Achaemenid Empire army and as a follower of past religion with the holy structure and worshiper. These motifs are clearly depicted in Ghizghapan, Dukkan-e-Daud and Eshaghvand catacombs. Therefore, the king presented himself to the foreigners and remind his legitimation to the natives. Artaxerxes became the king after Bagadat and his coins are similar to the second set of Bagadat coins. These two kings could establish a semi-independence government in Persis. The third king who called himself a Frataraka king was Vahbarz and as it is said, the most researchers suggest that in his reign Persis ruled completely independent. It is not acceptable according to the historical stories and the wars between Seleucid and Parthian kings. His successor was Autophradates I and based on the mentioned references and evidences in the paper, Persis had achieved a full independence during his reign and the Persis independence was all gone when his reign was over and the local government administered as semi-independence until Artaxerxes IV (the Sassanid Artaxerxes I) sat on the throne. We see new motifs on the Autophradates coins, which originated from xenophobia and independence thoughts. These motifs included the bow and Farvahr. As for the bow, the king presents himself as the absolute power of Persis and, as Achaemenid kings, he is capable of confronting enemy and preserve the holy land of Persepolis. For the Farvahr symbol, the king clearly manifests his power from neither people nor foreigners but Ahura Mazda as the powerful Achaemenid kings he also chosen by the Gods. The present study suggests that with the independence of Persis in Autophradates reign, new symbols and motifs reminding the absolute power of Achaemenid kings minted on coins and it was not possible unless there were no foreign power in control in Persis kingdom.